2007
DOI: 10.4049/jimmunol.178.8.5166
|View full text |Cite
|
Sign up to set email alerts
|

Oligoadenylate Synthetase/Protein Kinase R Pathways and αβ TCR+ T Cells Are Required for Adenovirus Vector: IFN-γ Inhibition of Herpes Simplex Virus-1 in Cornea

Abstract: An adenoviral (Ad) vector containing the murine IFN-γ transgene (Ad:IFN-γ) was evaluated for its capacity to inhibit HSV-1. To measure effectiveness, viral titers were analyzed in cornea and trigeminal ganglia (TG) during acute ocular HSV-1 infection. Ad:IFN-γ potently suppressed HSV-1 replication in a dose-dependent fashion, requiring IFN-γ receptor. Moreover, Ad:IFN-γ was effective when delivered −72 and −24 h before infection as well as 24 h postinfection. Associated with antiviral opposition, TG from Ad:IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…We found a significant increase in gene expression of IFN-γ in the cornea of rabbits treated for seven days. Early studies have shown that IFN-γ has a protective effect during infection (Austin et al, 2007; He et al, 1999; Minami et al, 2002). It has been reported that in mice, IFN-γ reduces replication of the HSV-1 virus in the TG by a mechanism that involves CD8+T cells and reduction of infected early protein 0 (ICP0) expression.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant increase in gene expression of IFN-γ in the cornea of rabbits treated for seven days. Early studies have shown that IFN-γ has a protective effect during infection (Austin et al, 2007; He et al, 1999; Minami et al, 2002). It has been reported that in mice, IFN-γ reduces replication of the HSV-1 virus in the TG by a mechanism that involves CD8+T cells and reduction of infected early protein 0 (ICP0) expression.…”
Section: Discussionmentioning
confidence: 99%
“…Plaques were visualized and enumerated with the aid of an inverted microscope 24 to 48 hours later and quantified as mean log plaque-forming units per pair of corneas or per cornea, as previously described. 27 …”
Section: Viral Plaque Assaymentioning
confidence: 99%
“…by plaque assay as previously described. 18 P. aeruginosa levels were determined in the designated tissues at indicated times p.i. following homogenization of tissue in sterile PBS and plating of serially diluted sample on agar plates.…”
Section: Corneal Infectionmentioning
confidence: 99%